Short Course on Water Law for the Eastern United States - Earl Finbar Murphy (Washington University Law Quarterly, 1961)
Until the past generation, problems in water law have been regarded as exclusively the concern of jurisdictions possessing either arid or saturated lands. The increasing industrialization and urban concentration occurring since 1900 have radically altered this attitude. Nowhere is this more strikingly shown than in the United States. In this country water use rose from 40 billion gallons per day in 1900 to 92 billion in 1930, and 312 billion in 1960. For the entire period, the total readily available fresh water supply has been 515 billion gallons per day. By 1975 it is predicted the United States will be drawing 453 billion of this each day and, in order to safeguard such demands, will require a quantity of water one third more than the total supply. This physical miracle is to be performed through techniques for the conversion of saline and brackish waters, which pose engineering and economic difficulties requiring Herculean solutions. Because these changes are to occur in the eastern United States, which presently has 55 per cent of the nation's population and 65 per cent of its industry; and because this is the area previously regarded as unaffected by water problems, an examination of the pertinent law is in order in this interval between the realization of impending doom and the coming of the anticipated technical salvation.
Keywords: Water and watercourses